Kalantaevska G. P. The activity of Spiridon Cherkasenko as a publicist in the social life of Ukraine at the beginning of XX th century - Kalantaevska G. P (Philological Treatises, 2020)
This article deals with S. Cherkasenko’s activity in public, literary, educational and pedagogical life of Ukrainian society in XX th century. It analyses the most famous journalistic works of the writer, in which he expresses his views on education, proclames national liberation ideas based on analyses of historical events, literary and artistic classics